2018
DOI: 10.1007/jhep03(2018)113
|View full text |Cite
|
Sign up to set email alerts
|

The light bound states of $$ \mathcal{N}=1 $$ supersymmetric SU(3) Yang-Mills theory on the lattice

Abstract: In this article we summarise our results from numerical simulations of N = 1 supersymmetric Yang-Mills theory with gauge group SU(3). We use the formulation of Curci and Veneziano with clover-improved Wilson fermions. The masses of various bound states have been obtained at different values of the gluino mass and gauge coupling. Extrapolations to the limit of vanishing gluino mass indicate that the bound states form mass-degenerate supermultiplets.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…Comparing Left: 0 ++ 'glueball' and fermionic 'gluino-glue' particle masses vs. the 'adjoint pion' mass squared, from Ref. [108]. The m 2 π → 0 extrapolations of these masses agree within uncertainties even at a fixed lattice spacing, supporting the formation of supermultiplets expected in the chiral continuum limit.…”
Section: Minimally Supersymmetric Yang-mills (N = 1 Sym) In Four Dimementioning
confidence: 63%
See 1 more Smart Citation
“…Comparing Left: 0 ++ 'glueball' and fermionic 'gluino-glue' particle masses vs. the 'adjoint pion' mass squared, from Ref. [108]. The m 2 π → 0 extrapolations of these masses agree within uncertainties even at a fixed lattice spacing, supporting the formation of supermultiplets expected in the chiral continuum limit.…”
Section: Minimally Supersymmetric Yang-mills (N = 1 Sym) In Four Dimementioning
confidence: 63%
“…3 shows recent SU(3) results from Ref. [108] for the masses of two composite states expected to form (part of) a degenerate multiplet in the supersymmetric continuum chiral limit [114,115]: the 0 ++ 'glueball' and the fermionic 'gluino-glue' particle. Even at a fixed lattice spacing the chiral extrapolations of these masses agree within uncertainties.…”
Section: Minimally Supersymmetric Yang-mills (N = 1 Sym) In Four Dimementioning
confidence: 97%
“…Supersymmetry is explicitly broken by the lattice formulation, but for this theory it has been shown that it is sufficient to restore chiral symmetry in the continuum limit to recover supersymmetry [1]. The mass spectrum and chiral properties of SYM theory have been extensively studied on the lattice with Wilson fermions for the gauge groups SU(2) [2] and SU(3) [3,4]. The next step towards a supersymmetric standard model is the inclusion of matter fields in the fundamental representation, leading to supersymmetric QCD (SQCD).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the light superpartners of known particles may serve as candidates for dark matter in our universe. The research presented in these proceedings is focused on four-dimensional supersymmetric quantum chromodynamics (Super-QCD) [1,2] and its essential building block, the N = 1 Super-Yang-Mills (SYM) theory with gauge group SU (3). To study the non-perturbative features of this theory, we employ lattice simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To study the non-perturbative features of this theory, we employ lattice simulations. Related investigations are performed by the DESY-Münster collaboration [3,4,5].…”
Section: Introductionmentioning
confidence: 99%